«Tire la chevillette, la bobinette cherra!»: Quattro traduzioni italiane di “Le Petit Chaperon rouge” di Charles Perrault dal Settecento al Duemila (Ticontre. Theory Text Translation, 2022)
Published in 1697, Charles Perrault’s fairy-tale Le Petit Chaperon rouge has been the subject of numerous versions and adaptations. This study focuses on four Italian translations published between the 18th and 21st centuries, chosen for their significance. Through the analysis of tex- tual and paratextual elements, an attempt will be made to bring out the operational ‘regime’ of translation (P. Burke), with reference to the rendering of the formulaic language that strongly characterises this fairy-tale. The perspective of Descriptive Translation Studies will allow us to appre- ciate the project behind each translation, while showing the different versions of the fairy-tale as a precious mirror of their time.